Correlation of Smoking and National Institutes of Health Stroke Scale (NIHSS) in Acute Ischemic Stroke Patients - Yunike Tourisiana1, Mohammad Saiful Islam1, Joseph Ekowahono Rahardjo1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Ischemic stroke is the most common type of stroke with 87.00% prevalence of atherosclerosis as one of the causes of cerebral vascular lumen occlusion. Smoking is known as a modifiable risk factor for stroke. The process of atherosclerosis leads to a neurological deficit resulting in impairment of the patient. One of the scales used to assess impairment is the National Institutes of Health Stroke Scale (NIHSS).Objectives: To know the correlation between smoking status and functional degree of acute ischemic stroke patients as measured by NIHSS.Method: The subjects were 48 patients. The study design was cross-sectional and clinical sampling consecutive admissions and an acute ischemic stroke image imaging. Smoking status data was obtained through anamnesis at the time the patient was hospitalized supported by the testimony of the immediate family. NIHSS values were obtained on the first day of hospitalization. Data analysis used chi-square test and logistic regression.Result: Sex (p = 0.001) and smoking (p = 0.013) were variables that had significant correlations with NIHSS. There was no association between smoking and the functional degree of acute ischemic stroke patients measured by NIHSS, (p = 0.57) with Adjusted Odds Ratio 1.5 (CI 95% 0.35 - 6.9).Conclusion: There was no significant association between smoking with functional degree of acute ischemic stroke patients as measured by NIHSS.